2012
DOI: 10.1111/j.1468-2389.2012.00589.x
|View full text |Cite
|
Sign up to set email alerts
|

Personal Values, Autonomy, and Self‐efficacy: Evidence from frontline service employees

Abstract: Employee's self‐efficacy has been related with important outcomes for organizations, such as service quality and job performance. Thus, understanding the antecedents of self‐efficacy can have important payoffs. Accordingly, this paper investigates how personal values interact with autonomy to affect employee's self‐efficacy. The hypotheses are tested with a sample of bank employees. The results reveal that conservation is negatively related to self‐efficacy and that both openness to change and self‐enhancement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
58
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 84 publications
9
58
1
4
Order By: Relevance
“…However, independent (autonomous) functioning is essential and a starting point in SCS lectures. The SCS lecturer stimulates autonomous behaviour and choices from the students (Sousa et al 2012).…”
Section: Scs Module In Practice In Higher Engineering Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, independent (autonomous) functioning is essential and a starting point in SCS lectures. The SCS lecturer stimulates autonomous behaviour and choices from the students (Sousa et al 2012).…”
Section: Scs Module In Practice In Higher Engineering Educationmentioning
confidence: 99%
“…During the learning process of the lecturer-researcher in the preliminary research, the Field experiment, a need for a deeper insight into the intrinsic motivation and personal development of Engineering students originated (Sousa et al 2012). The idea came into being that stimulating the conscious personal development of students during their Engineering studies requires more time and space, than given to the SCS module in the curriculum, to make individual students aware of the growth and development of their personal qualities.…”
Section: Case Studymentioning
confidence: 99%
“…Numerous studies in a range of occupational settings (e.g. clinical, educational and organisational) have provided empirical evidence that selfefficacy predicts and improves work performance, behaviour and learning Sousa et al, 2012). Research conducted in work settings, and in the context of workplace learning, has shown that self-efficacy serves as a precondition for workrelated learning .…”
Section: Self-efficacymentioning
confidence: 99%
“…Therefore, organisations can benefit from taking professionals' personal initiative and self-efficacy into account when making recruitment decisions Sousa et al, 2012). Furthermore, facilitating work conditions that appreciate and reinforce professionals' initiative-taking work behaviour by, for example, personal initiative training sessions and promotion systems, as well as appreciations and support from supervisors and top management, could pay off for organisations .…”
Section: Conclusion and Practical Implicationsmentioning
confidence: 99%
“…Its needs was to be built from literature reviews. Self-efficacy contributed to cognitive development and functioning (Bandura, 1993., Sousa et al, 2012. Employee's self-efficacy has been related with the importance one of organizational outcomes such as service quality and job performance.…”
Section: Theory-based Evaluationmentioning
confidence: 99%